Pathogenesis of Helicobacter pylori-Related Gastroduodenal Diseases from Molecular Epidemiological Studies - Yoshio Yamaoka (Gastroenterology Research and Practice)
Helicobacter pylori is a major human pathogen that infects the stomach and produces inflammation that is responsible for various gastroduodenal diseases. Despite the high prevalence of H. pylori infections in Africa and South Asia, the incidence of gastric cancer in these areas is much lower than in other countries. The incidence of gastric cancer also tends to decrease from north to south in East Asia. Data from molecular epidemiological studies show that this variation in different geographic areas could be explained in part by different types of H. pylori virulence factors, especially CagA, VacA, and OipA. H. pylori infection is thought to be involved in both gastric cancer and duodenal ulcer, which are at opposite ends of the disease spectrum. This discrepancy can also be explained in part by another H. pylori factor, DupA, as well as by CagA typing (East Asian type versus Western type). H. pylori has a genome of approximately 1,600 genes; therefore, there might be other novel virulence factors. Because genome wide analyses using whole-genome sequencing technology give a broad view of the genome of H. pylori, we hope that next-generation sequencers will enable us to efficiently investigate novel virulence factors.